Wnt signaling in prostate development and carcinogenesis - Kharaishvili, Gvantsa; Simkova, Dana; Makharoblidze, Eka; Trtkova, Katerina; Kolar, Zdenek; Bouchal, Jan (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2011)
BACKGROUND: The Wnt signaling pathway is crucial for cell fate decisions, stem cell renewal, regulation of cell proliferation and differentiation. Deregulated Wnt signaling is also implicated in a number of hereditary and degenerative diseases and cancer. METHODS AND RESULTS: This review highlights the role of the Wnt pathway in the regulation of stem/progenitor cell renewal and prostate gland development and how this signaling is altered in prostate cancer. Recent evidence suggests that Wnt signaling regulates androgen activity in prostate cancer cells, enhances androgen receptor expression and promotes the growth of prostate cancer even after androgen ablation therapy. There is also strong evidence that Wnt signaling is enhanced in androgen-ablation resistant tumors and bone metastases. CONCLUSIONS: Further study of the modulators of this pathway will be of therapeutic relevance as inhibition of Wnt signaling may have the potential to reduce the self-renewal and aggressive behaviour of prostate cancer while Wnt signaling activation might enhance stem cell activity when tissue regeneration is required.
Keywords: Prostatic Neoplasms; signální transdukce; prostata; nádory prostaty; Signal Transduction; Stem Cells; kmenové buňky; Animals; Humans; Wnt Proteins; mužské pohlaví; Male; lidé; proteiny Wnt; Prostate; zvířata